Krąg rodziców i dzieci uprawnionych do posiadania karty dużej rodziny a konstytucyjna zasada równości wobec prawa: [Parents and children entitled to hold of the large family card vs. the constitutional principle of equality before the law] (Studia Prawnicze / The Legal Studies, 2015)
W dniu 1 stycznia 2015 r.1 weszła w życie ustawa z dnia 5 grudnia 2014 r. o Karcie Dużej Rodziny. Zastąpiła ona rozwiązanie funkcjonujące jako rządowy program pomocy społecznej przyjęty przez Radę Ministrów w oparciu o upoważnienie wynikające z art. 24 ustawy z dnia 12 marca 2004 r. o pomocy społecznej, tj. rządowy program dla rodzin wielodzietnych powołany do życia uchwałą nr 85 z dnia 27 maja 2014 r. oraz rozporządzenie z dnia 27 maja 2014 r. w sprawie szczegółowych warunków realizacji tego programu. The subject of the article is the justification of the thesis that the differentiation of the legal situation of parents on the basis of the Act on the Large Family Card, who have established a family with at least three children violates the constitutional principle of equality before the law. On the one hand some parents are entitled to use the card without any time limit, and on the other hand there is a group of parents who also have large families, but are totally deprived of the right. According to the author of the article, the diversity does not represent any constitutionally protected value and the discrimination occurs due to the unlimited duration of the right to own the Card by eligible parents. The result of the above, as well as the fourth (another) child’s right to the Card depending on holding the Card by the parent, is discriminatory for the children born as the fourth (next) child in the family. The article is also an attempt to answer the question which way would be the best to remove the above-mentioned discrimination thus making it most coherent with the objective and content of the analyzed regulation.